THE ROLE OF THE PEDAGOGICAL ACTIVITY OF MODERN ENLIGHTENERS IN IMPROVING HUMAN VALUE AND QUALITY IN TODAY'S SOCIETY - Kimsanboev Rakhmonjon Valizoda (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
In this article, the educational activities of Turkestan Jadid enlighteners and their importance in increasing the human value and quality of education in the society have been revealed. Also, the article deeply analyzes the importance of the enlightenment efforts of the moderns in the development of today's education system.